Legal Analysis of the National Land Agency in Resolving Communal Land Disputes Among the Indigenous People of Bali (Lembaga Contrarius Indonesia, 2026)
This research analyzes the role and authority of the National Land Agency (BPN) in resolving communal land rights (hak ulayat) disputes among the indigenous communities in Bali from a normative juridical perspective. Communal land rights, as the communal rights of indigenous communities over land, often lead to conflicts with development interests and individual ownership. The BPN, as the authorized institution in land administration, plays a crucial role in mediating, facilitating, and resolving these disputes. This study employs a literature review approach, examining various relevant laws and regulations, court decisions, academic journals, and books. The findings indicate that the existing legal framework does not yet fully provide adequate protection for the communal land rights of Balinese indigenous communities. Therefore, harmonization of regulations and a more participatory approach in dispute resolution are needed. The implication of this research is the importance of comprehensive recognition and protection of communal land rights within the national land law framework.